Influence of Rainfall Changes on the Temperature Regime of Permafrost in Central Yakutia - Aleksandr Zhirkov; Petr Permyakov; Zhi Wen; Anatolii Kirillin (Land, 2021)
Climate change effects, such as melting of glaciers and sea ice in response to rising temperatures, may lead to an increase in global water availability and thus in precipitation. In Central Yakutia, as one of the possible options for climate change, an increase in rainfall is possible, which makes up more than 60% of the annual precipitation. Rainfall is a highly variable meteorological parameter both spatially and temporally. In order to assess its effect on the ground temperature regime in Central Yakutia, we conducted manipulation and numerical experiments with increased rainfall. The manipulation experiment results suggest that a significant (three-fold) increase in rainfall can lower the mean annual ground temperatures locally. The long-term simulation predicts that a 50% increase in rainfall would have a warming effect on the ground thermal regime on a regional scale. For Central Yakutia, infiltration of increased precipitation has been shown to have both warming and cooling effect depending on the area affected.